THE INFLUENCE OF THE PRINCIPAL’S ATTENNTION ON THE EFFECTIVENESS OF THE SCHOOL, MEDIATED BY THE ORGANIZATIONAL CLIMATE AND TEACHER’S ORGANIZATIONAL CITIZENSHIP BEHAVIOR - Kibtiyah, Intannisa Nur; Karyaningsih, RR Ponco Dewi; Marsofiyati (Jurnal Pendidikan Ekonomi, Perkantoran, dan Akuntansi, 2022)
The purpose of this study was to determine the influence of the principal's attention on school effectiveness, mediated by the organizational climate and organizational citizenship behavior of state vocational school teachers in Depok. The research method that the researchers used was a survey method with a descriptive approach, the population used was vocational high school teachers in Depok with a sample of 113 teachers. The model in this study uses a path analysis model. The analysis technique used in this study used an SEM (Structural Equation Modeling) model operated with the SmartPLS version 3.0 program for hypothesis testing.